2008
DOI: 10.1303/aez.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of certain insecticidal plants for the control of vector mosquitoes viz. Culex quinquefasciatus, Anopheles stephensi and Aedes aegypti

Abstract: Petroleum ether extracts of 63 varieties of plant species, including 37 varieties of leaves, 14 varieties of seeds, 10 varieties of flowers and 2 varieties of fruits were tested for larvicidal activity against 3rd instar larvae of important vector mosquitoes i.e. Culex quinquefasciatus, Anopheles stephensi and Aedes aegypti (Diptera: Culicidae). A 24 h bioassay showed that six plant extracts, Acacia nilotica, Argemone mexicana (leaves and seeds), Citrullus colocynthis, Jatropha curcas and Withania somnifera we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 6 publications
(3 reference statements)
7
38
0
1
Order By: Relevance
“…The insecticidal properties of several plant extracts such as (Razavi and Ahmadi 2016). Toxicological effects of Ashwagandha have also been observed against the larvae/adults of various insects, for instance, leaf extracts against larvae of Culex quinquefasciatus (Karmegam et al 1997), leaf, stem, fruit and root extracts against adults of Callosobruchus chinensis (Gupta and Srivastava 2008), leaf, fruit and root extracts against adult Sitophilus oryzae (Yankanchi and Gadache 2010;Suvanthini et al 2012), green and red fruit, seed, fruit without seeds, leaf and root extracts against Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus (Sakthivadivel and Daniel 2008;Bansal et al 2011), root, stem and leaf extracts against larvae of Tribolium castaneum (Arora et al 2011), and leaf extracts against larvae and adults of Oryzaephilus surinamensis (Madkaur et al 2013). Furthermore, acaricidal activity by the leaves of this medicinal plant against the larvae of deltamethrin resistant Hyalomma anatolicum (Singh et al 2014a) and fully engorged females of synthetic pyrethroid resistant Rhipicephalus microplus (Singh et al 2014b) have been shown.…”
Section: Discussionmentioning
confidence: 99%
“…The insecticidal properties of several plant extracts such as (Razavi and Ahmadi 2016). Toxicological effects of Ashwagandha have also been observed against the larvae/adults of various insects, for instance, leaf extracts against larvae of Culex quinquefasciatus (Karmegam et al 1997), leaf, stem, fruit and root extracts against adults of Callosobruchus chinensis (Gupta and Srivastava 2008), leaf, fruit and root extracts against adult Sitophilus oryzae (Yankanchi and Gadache 2010;Suvanthini et al 2012), green and red fruit, seed, fruit without seeds, leaf and root extracts against Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus (Sakthivadivel and Daniel 2008;Bansal et al 2011), root, stem and leaf extracts against larvae of Tribolium castaneum (Arora et al 2011), and leaf extracts against larvae and adults of Oryzaephilus surinamensis (Madkaur et al 2013). Furthermore, acaricidal activity by the leaves of this medicinal plant against the larvae of deltamethrin resistant Hyalomma anatolicum (Singh et al 2014a) and fully engorged females of synthetic pyrethroid resistant Rhipicephalus microplus (Singh et al 2014b) have been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanolic extracts of the leaves of Solanum xanthocarpum showed larvicidal activity against third and fourth instar larvae of C. quinquefasciatus (3) , with LC 50 values of 271.12 and 377.40mg/L, respectively. Sakthivadivel and Daniel (4) demonstrated the larvicidal effect of the ethanolic extract of leaves of Solanum trilobatum on fourth instar larvae of C. quinquefasciatus, with an LC 50 value >200mg/L. In a recent study (5) , methanolic extract and extract fractions from unripe S. lycocarpum fruit showed larvicidal effects against C. quinquefasciatus, with LC 50 values of 75.13-207.05mg/L.…”
Section: Fruit Of S Lycocarpummentioning
confidence: 97%
“…Ethanolic extracts of the leaves of S. xanthocarpum also showed activity against third and fourth instar larvae of C. quinquefasciatus (4) , with LC 90 values of 1,011.89 and 1,058.85mg/L, respectively. Changbunjong et al (11) showed that ethanolic extract of unripe S. xanthocarpum fruit had larvicidal activity against C. quinquefasciatus, with LC 50 and LC 90 values of 573.20 and 1,066.93mg/L, respectively, indicating that the extract was less toxic than that tested in this study.…”
Section: Introductionmentioning
confidence: 95%
“…In Bengal, flowers are given with honey for coughs and cold to children (Khare 2004). Several researchers reported the insecticidal property of Leucas (Srinivasan 2011;Vinayagam et al 2008;Sakthivadivel and Daniel 2008).…”
mentioning
confidence: 99%